Mechanisms of secondary brain damage from trauma and ischemia : recent advances of our understanding - Baethmann, Alexander (Springer, 2004)
Top level clinical and laboratory scientists present their most recent clinical and experimental findings and concepts. The well balanced contributions illustrate the enormous significance of the dialogue between both laboratory and clinic, ultimately for the benefit of the patients, and contribute to a better understanding of secondary brain damage from trauma and ischemia as basis to develop more effective treatment including drugs.
Acta neurochirurgica, ISSN 0065-1419 suppl. 89
Keywords: nemoci mozku; Brain Ischemia; Brain Diseases; Brain Infarction; Brain Injuries; poranění mozku; Brain Damage, Chronic; neurologie; Craniocerebral Trauma; chronické poškození mozku; mozkový infarkt; kraniocerebrální traumata; ischemie mozku